Employee Performance Reviewed From Incentive Given, Competence, Career Development And Employee Satisfaction (Study At Pku Muhammadiyah Hospital Surakarta) - Keny Sulistyorini; Istiatin Istiatin; Sudarwati Sudarwati (Jurnal Ners, 2025)
Hospitals, being service organizations, have a close link with resource management, including facilities, infrastructure, and human resources (HR), which include a diverse range of professions and a huge workforce. This study aims to examine the impact of incentives, competence, career development, and employee satisfaction on employee performance. This research approach employs quantitative research. The investigation was conducted at PKU Muhammadiyah Surakarta Hospital over a six-month period. The study's population consisted of 887 personnel from PKU Muhammadiyah Surakarta Hospital. This study used simple random sampling procedures to select 89 respondents. Data was collected using questionnaire approaches. Data analysis procedures included classical assumption tests, multiple linear regression tests, F tests, t tests, and coefficients of determination (R2). The findings revealed that incentives, competence, career development, and employee satisfaction had a substantial positive impact on staff performance at PKU Muhammadiyah Surakarta Hospital. The determination coefficient test yielded an Adjusted R2 value of 0.553, or 55.3%, indicating that incentive provision, competence, career development, and employee satisfaction influence employee performance at PKU Muhammadiyah Surakarta Hospital, with the remaining 44.7% explained by other variables